A Descriptive Quantitative Analysis on the Extent of Polypharmacy in Recipients of Ontario Primary Care Team Pharmacist-Led Medication Reviews - Nichelle Benny Gerard; Annalise Mathers; Christoph Laeer; Eric Lui; Tom Kontio; Payal Patel; Lisa Dolovich (MDPI AG, 2020)
Pharmacist-led medication reviews have been shown to improve medication management, reducing the adverse effects of polypharmacy among older adults. This paper quantitatively examines the medications, medication discrepancies and drug therapy problems of recipients in primary care. A convenience sample of 16 primary care team pharmacists in Ontario, Canada contributed data for patients with whom they conducted a medication review over a prior four-week period. Data were uploaded using electronic data capture forms and descriptive analyses were completed. Two hundred and thirty-seven patients (on average, 67.9 years old) were included in the study, taking an average of 9.2 prescription medications (<semantics>±</semantics>4.7). Majority of these patients (83.5%) were categorized as polypharmacy patients taking at least five or more prescribed drugs per day. Just over half of the patients were classified as having a low level of medication complexity (52.3%). Pharmacists identified 2.1 medication discrepancies (<semantics>±</semantics>3.9) and 3.6 drug therapy problems per patient (<semantics>±</semantics>2.8). Half these patients had more than one medication discrepancy and almost every patient had a drug therapy problem identified. Medication reviews conducted by pharmacists in primary care teams minimized medication discrepancies and addressed drug therapy problems to improve medication management and reduce adverse events that may result from polypharmacy.